2016
DOI: 10.1016/j.dnarep.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between APC and Fen1 during breast carcinogenesis

Abstract: Aberrant DNA base excision repair (BER) contributes to malignant transformation. However, inter-individual variations in DNA repair capacity plays a key role in modifying breast cancer risk. We review here emerging evidence that two proteins involved in BER – adenomatous polyposis coli (APC) and flap endonuclease 1 (Fen1) – promote the development of breast cancer through novel mechanisms. APC and Fen1 expression and interaction is increased in breast tumors versus normal cells, APC interacts with and blocks F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 144 publications
0
26
0
Order By: Relevance
“…It has been reported that frequent and long-term use of nonsteroidal anti-inflammatory drugs is associated with decreased odds of cervical cancer [11]. Increase in APC expression level also is associated with decreased risk of cancer [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that frequent and long-term use of nonsteroidal anti-inflammatory drugs is associated with decreased odds of cervical cancer [11]. Increase in APC expression level also is associated with decreased risk of cancer [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 97%
“…This gene encodes a tumor suppressor protein that acts as an antagonist of the Wnt signaling pathway that regulates crucial aspects of cell fate determination, cell migration, cell polarity, neural patterning and organogenesis during embryonic development. This protein can modulate the BER pathway through an interaction with the DNA polymerase β (Pol-β) and the ap endonuclease 1 (Fen-1) and consequently might play an important role in carcinogenesis and chemotherapy by determining whether cells with DNA damage survive or undergo apoptosis 51,52 . In breast tumors, the transcriptional silencing of the APC gene by promoter hypermethylation has been detected in up to 70% of in ammatory human breast tumors 53 and 7% of metaplastic breast carcinomas 54 .…”
Section: Discussionmentioning
confidence: 99%
“…[10] It has also been shown that inhibition of caspase-9 may block the autophagic flux and enhance cell death due to blockage of cytoprotective autophagy [11]. Previous experiments have demonstrated that non-steroidal anti-inflammatory drugs (NSAIDs) have chemopreventive effects on several cancers including those of cervix [12]. Diclofenac has shown anti-neoplastic effects by downregulating PI3-K/Akt/PTEN pathway and also inducing apoptosis [13].…”
Section: Discussionmentioning
confidence: 99%